Multifunctional cytokine production reveals functional superiority of memory CD4 T cells. Issue 11 (13th June 2019) - Westerhof, Lotus M; McGuire, Kris; MacLellan, Lindsay; Flynn, Ashley; Gray, Joshua I; Thomas, Matthew; Goodyear, Carl S; MacLeod, Megan KL
Abstract: T cell protective immunity is associated with multifunctional memory cells that produce several different cytokines. Currently, our understanding of when and how these cells are generated is limited. We have used an influenza virus mouse infection model to investigate whether the cytokine profile of memory T cells is reflective of primary responding cells or skewed toward a distinct profile. We found that, in comparison to primary cells, memory T cells tended to make multiple cytokines simultaneously. Analysis of the timings of release of cytokine by influenza virus‐specific T cells, demonstrated that primary responding CD4 T cells from lymphoid organs were unable to produce a sustained cytokine response. In contrast CD8 T cells, memory CD4 T cells, and primary responding CD4 T cells from the lung produced a sustained cytokine response throughout the restimulation period. Moreover, memory CD4 T cells were more resistant than primary responding CD4 T cells to inhibitors that suppress T cell receptor signaling. Together, these data suggest that memory CD4 T cells display superior cytokine responses compared to primary responding cells. These data are key to our ability to identify the cues that drive the generation of protective memory CD4 T cells following infection. Abstract : Influenza virus‐specific memory CD4 T cells are more likely to be multifunctional and produce a more sustained cytokine response than primary responding T cells.